Analisis Hambatan Proses Belajar Biologi dan Cara Pemecahannya Dalam Pelaksanaan Pembelajaran Jarak Jauh - Harlis Harlis*; Retni Sulistiyoning Budiarti (Universitas Syiah Kuala, 2021)
Currently, one form of implementing learning during the pandemic is distance learning. The process of learning biology during the pandemic presents various problems in the delivery of material. This study aims to look at the barriers and ways to solve them in distance learning during the COVID-19 pandemic. The study used a qualitative descriptive research design with data collection techniques in the form of observation, interviews and documentation techniques. The subjects of this research are teachers in the field of biology studies who have implemented distance learning with various brave application platforms in the hope of providing data related to distance learning barriers who act as informants; as well as students who experience obstacles in the implementation of distance learning. The results of the study obtained several obstacles in distance learning in biology learning, namely 1) obstacles in the learning process of learning materials which in using the application not all have Android cellphones, the network is not good during the learning process, and the level of student boredom. 2) obstacles in the interaction process in the learning process which usually appear on the subject or material that is difficult for students to understand. 3) the strength of the empowerment of facilities and elements in internet network learning is weak, running out of quota, and there are some students who do not have electronic devices. 4) obstacles in managing teaching materials to be delivered in the learning process that still need accuracy in choosing the right teaching materials